Effectiveness of three antigen retrieval techniques for use in immunostaining of formalin-fixed schistosoma japonicum egg antigens in mouse granulomatous livers - Guillergan, Fred P.
Antigen retrieval systems have expanded the scope of immunohistochemical studies. Various antigen-unmasking techniques were developed and utilized as pretreatment for formalin-fixed paraffin embedded tissues prior to immunological studies. Antigen retrieval systems are necessary for immunostaining of formalin-fixed specimens because it uncovers the epitopes masked by hydroxy-methylene bridges that cross-links macromolecules in and outside the cells.In this study, effectiveness of antigen retrieval systems was tested for immunohistochemistry studies. Schistosoma japonicum-infected mice gradulomatous liver tissues fixed in 10% neutral buffered formalin at either 20-hour or 30-day fixation periods were utilized. Effect of both fixation times on immunostaining was evaluated.Four procedures were used in this study, three for antigen retrieval systems and one for no antigen retrieval. The three methods employed as antigen retrieval prior to immunostaining included, (1) heat-introduced antigen retrieval (2) proteolytic enzyme digestion, and (3) combination of heat-introduced and enzyme digestion. For the heat-induced antigen retrieval, water bath was utilized to incubate specimens at 100 percent C for 20 minutes. Proteolyic enzyme digestion was done with 0.1% trypsin at 37 degrees C for 30 minutes. The third antigen retrieval system was a combination of heat-induced and enzyme digestion methods. The same procedure for heat-induced antigen retrieval was applied to the combination treatment but was followed immediately after by enzyme digestion with 0.1% trypsin for 15 minutes.Citrate buffer was used as the antigen retrieval solution. Polyclonal antibody from serum of infected mice was utilized as primary antibody. Immunohistochemistry was done using DAKO LSAB 2 kits, and the procedure was followed as provided by the kit.